PROBLEM OF AGE-DETERMINATION IN THE INDIAN MACKEREL, RASTRELLIGER KANAGURTA, BY MEANS OF SCALES AND OTOLITHS - Seshappa, G (Indian Journal of Fisheries, 2011)
The study of the scales of Rastrelliger kanagurta (Cuvier) collected from different centres during the period 1955-67 and 1969-70 showed that at all centres specimens below 21 cm in total length were without scale-rings; a small percentage of specimens in the • 21-22.9 cm group showed rings, while a large percentage among those above 23 cm total length showed the rings in all the centres, this percentage being the smallest (63.1 %) at Calicut and largest (94.3%) at Karwar. Two rings occurred frequently in specimens above 25 cm and up to four rings occurred in the very large specimens of Vizhinjam and Mandapam, but in these large specimens reading of the rings was difficult as they frequently became faint and obscured as a result of the thickening of the scales subsequent to the ring-formation. The scale-rings seem to be formed as a result of a physiological strain on the fish during the process of growth and ripening of the gonads and also spawning. When clear rings were not noticed in mackerel with gonads in advanced stages, there were thin margins, which indicated the beginning of ring formation. The otoliths did not show any annuli that could be used for age-determination